Surface guided radiotherapy practice in paediatric oncology: a survey on behalf of the SIOPE Radiation Oncology Working Group - Seravalli, Enrica; Kroon, Petra S; Bolle, Stephanie; Dunlea, Cathy; Harrabi, Semi B.; Laprie, Anne; Lassen-Ramshad, Yasmin; Whitfield, Gillian; Janssens, Geert O (British journal of radiology, 2024)
Surface guided radiotherapy (SGRT) is increasingly being implemented to track patient’s surface movement and position during radiation therapy. However, limited information is available on the SGRT use in paediatrics. The aim of this double survey was to map SIOPE (European Society for Paediatric Oncology)-affiliated centres using SGRT and to gain information on potential indications, observed, or expected benefits.A double online survey was distributed to 246 SIOPE-affiliated radiotherapy (RT) centres. Multiple choices, yes/no, and open answers were included. The first survey (41 questions) was active from February to March 2021. A shortened version (13 questions) was repeated in March 2023 to detect trends in SGRT use within the same community.Respectively, 76/142 (54%) and 28/142 (20%) responding centres used and planned to use SGRT clinically, including 4/34 (12%) new centres since 2021. Among the SGRT users, 33/76 (43%) already applied this technology to paediatric treatments. The main benefits of improved patient comfort, better monitoring of intrafraction motion, and more accurate initial patient set-up expected by future users did not differ from current SGRT-users (P = .893). Among non-SGRT users, the main hurdles to implement SGRT were costs and time for installation. In paediatrics, SGRT is applied to all anatomical sites.This work provides information on the practice of SGRT in paediatrics across SIOPE-affiliated RT centres which can serve as a basis for departments when considering the purchase of SGRT systems.Since little information is available in the literature on the use of SGRT in paediatrics, the results of this double survey can serve as a basis for departments treating children when considering the purchase of an SGRT system.